2023
DOI: 10.3390/children10040679
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Kawasaki Disease with Peripheral Facial Nerve Palsy and Lung Nodules: A Case Report and Literature Review

Abstract: The diagnosis of Kawasaki disease (KD) is challenging and often delayed mainly in case of young infants and in presence of an incomplete disease and atypical features. Facial nerve palsy is one of the rare neurologic symptoms of KD, associated with a higher incidence of coronary arteries lesions and may be an indicator of a more severe disease. Here, we describe a case of lower motor neuron facial nerve palsy complicating KD and perform an extensive literature review to better characterize clinical features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Maglione et al [5] reported a rare case of lower motor neuron facial nerve palsy as a complication of KD. In this particular case, the patient's diagnosis was made on the sixth day of the disease, and they also exhibited extensive coronary artery lesions.…”
mentioning
confidence: 99%
“…Maglione et al [5] reported a rare case of lower motor neuron facial nerve palsy as a complication of KD. In this particular case, the patient's diagnosis was made on the sixth day of the disease, and they also exhibited extensive coronary artery lesions.…”
mentioning
confidence: 99%